A new pest of tomato and other records of mealybugs (Hemiptera: Pseudococcidae) from Espírito Santo, Brazil - Culik, Mark P.; Gullan, Penny J. (Zootaxa, 2005)
Three mealybug (Hemiptera: Pseudococcidae) plant pest species: Dysmicoccus boninsis (Kuwana), Phenacoccus solenopsis Tinsley, and Pseudococcus viburni (Signoret), are recorded for the first time in the state of Espírito Santo, Brazil. This is the first record of Phenacoccus solenopsis in Brazil, where it was found infesting tomato plants. The species Antonina graminis (Maskell), a common pest of Bermuda grass, and Dysmicoccus brevipes (Cockerell), a major pest of pineapple, also were encountered.